Sulfated Polysaccharides from Chaetoceros muelleri: Macromolecular Characteristics and Bioactive Properties - Valeria Miranda-Arizmendi; Diana Fimbres-Olivarria; Anselmo Miranda-Baeza; Karla Martínez-Robinson; Agustín Rascón-Chu; Yubia De Anda-Flores; Jaime Lizardi-Mendoza; Mayra A. Mendez-Encinas; Francisco Brown-Bojorquez; Rafael Canett-Romero; Elizabeth Carvajal-Millan (Biology, 2022)
In the present study, a culture of Chaetoceros muelleri, a cosmopolitan planktonic diatom microalga present in the Sea of Cortez, was established under controlled laboratory conditions. A sulfated polysaccharide (CMSP) extraction was carried out from the biomass obtained, resulting in a yield of 2.2% (w/w of dry biomass). The CMSP sample was analyzed by Fourier transform infrared spectroscopy, showing bands ranging from 3405 to 590 cm−1 and a sulfate substitution degree of 0.10. Scanning electron microscopy with elemental analysis revealed that the CMSP particles are irregularly shaped with non-acute angles and contain sulfur. High-performance liquid chromatography coupled to a dynamic light-scattering detector yielded molecular weight (Mw), polydispersity index (PDI), intrinsic viscosity [η], and hydrodynamic radius (Rh) values of 4.13 kDa, 2.0, 4.68 mL/g, and 1.3 nm, respectively, for the CMSP. This polysaccharide did not present cytotoxicity in CCD-841 colon cells. The antioxidant activity and the glycemic index of the CMSP were 23% and 49, respectively, which gives this molecule an added value by keeping low glycemic levels and exerting antioxidant activity simultaneously.